PENGARUH METODE ELEMENTER DAN KONVENSIONAL MINAT TERHADAP KETERAMPILAN DASAR BOLAVOLI SISWA SMP NEGERI 29 PEKANBARU RIAU - Ahmadi, Dedi (Jurnal BOLA: Bersama Olahraga Laju Asia, 2018)
Based on the observations of researchers in the field shows that the male student SMP 29 Pekanbaru, volleyball basic engineering skills are still low, and there are many students who have not mastered the basic techniques of volleyball well, besides learning method used is not appropriate. The purpose of this study was to determine differences in the effect of learning methods and interest in playing volleyball skills.The research is a quasi-experimental, using a 2x2 factorial design. The population was male student of class VII and VIII SMP 29 Pekanbaru, amounting to 82 people, while the samples in this study were 82 students of class VII and VIII son after the distribution group (82x27% = 22) a high level of interest in learning and (82x27% = 22) the low level of interest in learning. The instrument used was a test volleyball basic level. Data were analyzed by ANOVA followed by two lines and Tuckey test.The results of data analysis showed that: (1) There are significant differences between the results of the skills to play volleyball elementary and conventional group (of F = 6.10> Ftable = 4.06), (2) There is interaction between learning method with learning interest (of F = 40.82> F table = 4:06), (3) in the interest of learning high category, the conventional skills of volleyball student group given conventional teaching method is better than the group given elementary learning methods (Qh = 3.92> Qt = 3.79), (4) in the interest of studying the low category , playing volleyball skills students are given a group of elementary learning method is better than the group given conventional learning methods (Qh = 8.86> Qt = 3.79).